A sinus shear deformation model for static analysis of composite steel-concrete beams and twin-girder decks including shear lag and interfacial slip effects. (January 2019) - Lezgy-Nazargah, M.; Vidal, P.; Polit, O.
Abstract: A beam model is developed for the static analysis of composite steel-concrete beams and twin-girder decks which takes into account the effects of shear lag phenomenon as well as the interfacial slip between the concrete slab and steel joists. A sinus distribution is considered for the axial displacements of the concrete slab and steel joists. This kinematic represents the transverse shear strain in the concrete slab and steel joists using a cosine function. The considered kinematic satisfies the boundary conditions of transverse shear stress on the top and bottom surfaces and does not need any shear correction factor. The shear lag effects are introduced by prescribing the warping shape of the slab cross-section and taking its intensity as axial unknowns. A conforming three-nodded 25-dof beam element is derived for numerical simulations. The presented model has been validated by comparing the obtained results with elasticity solutions, 3D finite element results and other analytical and numerical models available in the open literature. Highlights: A low cost finite element model is presented for the analysis of composite steel-concrete beams and twin-girder decks. The shear lag phenomenon is captured through introducing appropriate warping function for the slab cross-section. The transverse shear strain in the concrete slab and steel joists has been represented using a cosine function. Partial shear interaction between the slab and the steel beams is represented using the concept of spring layer model.